2023
DOI: 10.3389/fendo.2023.1111360
|View full text |Cite
|
Sign up to set email alerts
|

Different scan areas affect the detection rates of diabetic retinopathy lesions by high-speed ultra-widefield swept-source optical coherence tomography angiography

Abstract: IntroductionThe study aimed to determine the effect of the scanning area used for high-speed ultra-widefield swept-source optical coherence tomography angiography (SS-OCTA) on the detection rate of diabetic retinopathy (DR) lesions.MethodsThis prospective, observational study involved diabetic patients between October 2021 and April 2022. The participants underwent a comprehensive ophthalmic examination and high-speed ultra-widefield SS-OCTA using a 24 mm × 20 mm scanning protocol. A central area denoted as “1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Although a comparison of 24×20 mm 2 SS-OCTA with FFA in evaluating DR lesions showed good to moderate agreement, SS-OCTA had several advantages, including its noninvasiveness, lower cost, rapid performance, and reproducible results ( 22 ). A recent study analyzing the effect of scan area on the detection of DR lesions, by comparing 12 mm × 12 mm central and 24 mm × 20 mm images, found that the ultra-widefield SS-OCTA detected more intra-retinal microvascular and neovascular abnormalities, with higher rates of ischemia in the mid-peripheral than in the posterior retina ( 23 ). Another study found that ultra-widefield color fundus photography (UWF CFP) plus SS-OCTA and UWF CFP plus FFA showed good agreement in the rate of detection of DR lesions and DR severity grade ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although a comparison of 24×20 mm 2 SS-OCTA with FFA in evaluating DR lesions showed good to moderate agreement, SS-OCTA had several advantages, including its noninvasiveness, lower cost, rapid performance, and reproducible results ( 22 ). A recent study analyzing the effect of scan area on the detection of DR lesions, by comparing 12 mm × 12 mm central and 24 mm × 20 mm images, found that the ultra-widefield SS-OCTA detected more intra-retinal microvascular and neovascular abnormalities, with higher rates of ischemia in the mid-peripheral than in the posterior retina ( 23 ). Another study found that ultra-widefield color fundus photography (UWF CFP) plus SS-OCTA and UWF CFP plus FFA showed good agreement in the rate of detection of DR lesions and DR severity grade ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of WF-OCTA increased the detection rate of vascular abnormalities in DR compared to standard OCTA [25]. Both NP areas and the ischemic index were evaluated more precisely with 24 × 20 mm WF-OCT compared to 12 × 12 mm scans.…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…The 12 mm × 12 mm FOV corresponds to approximately 50°, offering a restricted view for assessing retinal microvasculature in DR.[ 42 ]…”
Section: U Ltra - Widefield O ...mentioning
confidence: 99%